Pojęcie i istota samorządu lokalnego: The concept and essence of local government - Bąbała, Wojciech; Kuniewicz, Monika; Pióro, Ewelina; Ryczkowska, Katarzyna; Wielgosz, Anna (Management and Administration Journal, 2021)
x